Diversity Assessment of Some Sesame (Sesamum indicum L.) Genotypes Cultivated in Northern Ghana Using Morphological and Simple Sequence Repeat (SSR) Markers - Raphael Adu-Gyamfi; Ruth Prempeh; Issahaku Zakaria (Advances in Agriculture)
In Ghana, sesame is cultivated in some districts of northern Ghana. Genotypes cultivated are land races that are low yielding leading to decline in production. There is the need for improvement of these land races to generate high yielding cultivars. Characterization of genetic diversity of the sesame land races will be of great value in assisting in parental lines selection for sesame breeding programmes in Ghana. Twenty-five sesame land races were collected from five districts in northern Ghana noted for sesame cultivation. Seeds collected were planted in three replicates in randomized complete block design and were evaluated for a number of morphological characters. Data collected were subjected to Principal Component Analysis (PCA) and a dendrogram showing similarity between the accessions were drawn. Data on number of capsules per plant, number of seeds per capsule, and plant height at flowering were subjected to analysis of variance using GenStat Discovery Edition 4. Molecular genetic diversity was assessed by using thirty eight SSR markers widely distributed across sesame genome to characterize the materials. Twenty-one out of the 38 primers were polymorphic. Cluster analyses using the Euclidean similarity test and a complete link clustering method were used to make a dendrogram out of the morphological data. Analysis of variance showed that capsule number was significantly different; a range of 54.9 and 146.7 was produced. The number of seeds per capsule varied significantly and the variation between highest and lowest accession in seed production was 33%. Plant height was also significantly different ranging from 60.6 to 94.1 cm. Using morphological traits the accessions clustered into two major groups and two minor groups and variation among accessions were 10-61%. On the other hand, SSR marker-based dendrogram revealed five major and two minor groups. It showed that variation among the accessions was low, 10-20%. Heterozygosity was 0.52, total alleles produced were 410, and average allele per locus was 19.52. Six accessions, C3, C4, S5, W1, W3, and W5 fell in five different clusters in the SSR dendrogram and in six clusters in the morphomolecular based dendrogram. These accessions were noted for high capsule number per plant and seeds number per capsule and are recommended for consideration as potential parental lines for breeding programme for high yield.